Influence of the Liquid Viscosity on the Formation of Bubble Structures in a 20 Khz Field - Gaete-Garreton, L; Vargas-Hernandez, y; Salinas-Barrera, V (Elsevier B.V., 2015)
The cavitation field in a cylindrical vessel bottom-insonified by a 19.7 kHz large area transducer is studied experimentally. By adding controlled amounts of Poly-Ethylene Glycol (PEG) to water, the viscosity of the liquid is varied between one- and nine-fold the viscosity of pure water. For each liquid, and for various displacement amplitudes of the transducer, the liquid is imaged by a high-speed camera and the acoustic field is measured along the symmetry axis. For low driving amplitudes, only a spherical cap bubble structure appears on the transducer, growing with amplitude, and the axial acoustic pressure field displays a standing-wave shape. Above some threshold amplitude of the transducer, a flare-like structure starts to build up, involving bubbles strongly expelled from the transducer surface, and the axial pressure profile becomes almost monotonic. Increasing more the driving amplitude, the structure extends in height, and the pressure profile remains monotonic but decreases its global amplitude. This behavior is similar for all the water-PEG mixtures used, but the threshold for structure formation increases with the viscosity of the liquid. The images of the bubble structures are interpreted and correlated to the measured acoustic pressure profiles. The appearance of traveling waves near the transducer, produced by the strong energy dissipated by inertial bubbles, is conjectured to be a key mechanism accompanying the sudden appearance of the flare-like structure. © 2014 Elsevier B.V. All rights reserved.